2018
DOI: 10.3221/igf-esis.45.02
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behavior Assessment of a Brazilian Heritage Construction

Abstract: Preservation of historical constructions, and passing it on to future generations, is a major issue in modern societies. Earthquakes are one of the major causes of damages to heritage buildings across the world. The city of Sobral (Ceará State, Brazil) keeps in its historic center a large number of heritage buildings and, since 2008, an intense seismic activity has been observed. This study aims to contribute to the preservation of the Sobral heritage constructions against seismic loads through the assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Considering the global seismic performance of the buildings in this study is in line with several previous published studies [10,16,20]. In contrast, investigations presented in Francisco Brandão et al [11], Hökelekli [18] and Maras et al [19] considered local damages in buildings using stress analysis by adopting linear or/and nonlinear time history analyses. On the other hand, several previous investigations considered both local and global performance of buildings [9,17].…”
Section: Analysis Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Considering the global seismic performance of the buildings in this study is in line with several previous published studies [10,16,20]. In contrast, investigations presented in Francisco Brandão et al [11], Hökelekli [18] and Maras et al [19] considered local damages in buildings using stress analysis by adopting linear or/and nonlinear time history analyses. On the other hand, several previous investigations considered both local and global performance of buildings [9,17].…”
Section: Analysis Resultssupporting
confidence: 83%
“…Gianni Bartoli et al [10] reported and compared results of first and third specified levels of assessments and draw the conclusions based on the third level that involves nonlinear static pushover analysis. Francisco Brandão et al [11] investigated the seismic resistance of the historical Nossa Senhora das Dores Church in Brazil using three dimensional finite element modeling. Linear time-history analyses were conducted considering two actual earthquake records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its failure can cause the ruin of the building and consequent material and immaterial loss. Relevant buildings in the historic center of Sobral has been diagnosed with pathologies (Mota et al , 2017; Fontenele et al , 2021), in addition, the municipality deals with sporadic seismic activities despite its intra-plate location (Oliveira et al , 2010; Brandão et al , 2018). These criteria comprise three subcriteria:Materials (Mat): The construction techniques and materials frequently with low control and reduced quality designate a need for periodic assessment of its physical integrity.Façade (Fac): It has a structural role conferring relevant rigidity in the scenario.…”
Section: Resultsmentioning
confidence: 99%
“…arthquakes are a natural phenomenon with violent shaking of the ground due to tectonic movements in the interior of the earth [1]. When the structure is subjected to seismic excitation there is an induction of horizontal forces at foundation level of structures which can generate vibration problems and in situations where the frequency of this excitation is very close to some natural frequency of the structure, the vibrations can reach large amplitude, allowing which the resonance phenomenon can occur, which can cause large displacements in the structure, and even its collapse [2][3][4]. In this scenario, the structural control is an alternative to reduce the levels of vibrations and E improve the performance of these structures when requested by dynamics actions.…”
Section: Introductionmentioning
confidence: 99%